Characterization of 2D colloid aggregations created by optically induced electrohydrodynamics. Issue 15 (3rd July 2015) - Work, Andrew H.; Williams, Stuart J.
Abstract : Rapid electrokinetic patterning (REP) is a technique for creating self‐assembled monolayers (SAMs) of spherical particles in a liquid medium, and dynamically controlling them though the simultaneous application of an electric field and optically induced temperature gradients. Previous work has investigated and characterized REP axisymmetric aggregations generated from a focus laser within a uniform electric field; work herein characterizes line‐shaped particle assemblies derived from the application of a linearly scanned laser. The resulting aggregations of spherical polystyrene particles (1 μm) suspended in low‐conductivity aqueous potassium chloride solution (KCl, 2.5 mS/m) resembled elliptical‐shaped crystalline geometries. The mean particle‐to‐particle spacing within the aggregation remained greater than 1.5 diameters for experiments herein (6.5 Vrms, 30 kHz) due to dipole–dipole repulsive forces. Interparticle spacing demonstrated a linear relationship (1.6–2.1 μm) with increasing scanning lengths (up to 83 μm), decreased from 1.9 to 1.7 μm with increasing scanning frequency (0.38–16 Hz) for a 53 μm scan length, and decreased from 2.0 to 1.6 μm with increasing laser power (11.9–18.8 mW) for a 59 μm, 16 Hz laser scan.